The impacts of dental filling materials on RapidArc treatment planning and dose delivery: Challenges and solution. Issue 8 (26th July 2013) - Mail, Noor; Albarakati, Y.; Ahmad Khan, M.; Saeedi, F.; Safadi, N.; Al‐Ghamdi, S.; Saoudi, A.
Abstract : Purpose: : The presence of high‐density material in the oral cavity creates dose perturbation in both downstream and upstream directions at the surfaces of dental filling materials (DFM). In this study, the authors have investigated the effect of DFM on head and neck RapidArc treatment plans and delivery. Solutions are proposed to address (1) the issue of downstream dose perturbation, which might cause target under dosage, and (2) to reduce the upstream dose from DFM which may be the primary source of mucositis. In addition, an investigation of the clinical role of a custom‐made plastic dental mold/gutter (PDM) in sparing the oral mucosa and tongue reaction is outlined. Methods: : The influence of the dental filling artifacts on dose distribution was investigated using a geometrically well‐defined head and neck intensity modulated radiation therapy (IMRT) verification phantom (PTW, Freiberg, Germany) with DFM inserts called amalgam, which contained 50% mercury, 25% silver, 14% tin, 8% copper, and 3% other trace metals. Three RapidArc plans were generated in the Varian Eclipse System to treat the oral cavity using the same computer tomography (CT) dataset, including (1) a raw CT image, (2) a streaking artifacts region, which was replaced with a mask of 10 HU, and (3) a 2 cm‐thick 6000 HU virtual filter [a volume created in treatment planning system to compensate for beam attenuation, where the thickness of this virtual filter is based on the measured percent depth dose (PDD) data and Eclipse calculation]. The dose delivery for the three plans was verified using Gafchromic‐EBT2 film measurements. The custom‐made PDM technique to reduce backscatter dose was clinically tested on four head and neck cancer patients (T3, N1, M0) with DFM, two patients with PDM and the other two patients without PDM. The thickness calculation of the PDM toward the mucosa and tongue was purely based on the measured upstream dose. Patients' with oral mucosal reaction was clinically examined initially and weekly during the course of radiotherapy. Results: : For a RapidArc treatment technique, the backscatter dose from the DFM insert was measured to be 9.25 ± 2.17 in the IMRT‐verification‐phantom. The measured backscatter upstream dose from DFM for a single‐field was 22% higher than without the DFM, whereas the downstream dose was lower by 14%. The values of homogeneity index for the plans with and without the application of mask were 0.09 and 0.14, respectively. The calculated mean treatment planning volume (PTV) dose differed from the delivered dose by 13% and was reduced to 2% when using the mask and virtual filter together. A grade 3 mucosa reaction was observed in the control group after 22–24 fractions (44–48 Gy). In contrast, no grade 3 mucositis was observed in the patients wearing the PDM after 25–26 fractions (50–52 Gy). Conclusions: : The backscatter from the DFM for a single, parallel‐opposed fields, and RapidArc treatment technique was found significant. The application of mask in replacing streaking artifacts can be useful in improving dose homogeneity in the PTV. The use of a virtual filter around the teeth during the planning phase reduces the target underdosage issue in the phantom. Furthermore, a reduction in mucositis is observed in the head and neck patients with the use of PDM.